Recent Advances in Matrix and Operator Theory - Ball, Joseph A. (Springer, 2017)
Many developments on the cutting edge of research in operator theory, matrix theory, coding theory, system theory, control theory and numerical linear algebra are reflected in this collection of original articles.The volume is of a cross-disciplinary nature. A number of papers are devoted to the analysis and algorithms for matrices with quasiseparable structure which is an active area of concurrent research in numerical linear algebra.